Commodities at a Glance: Special Issue on Shale Gas - United Nations Conference on Trade; Development (United Nations, 2019)
The Commodities at a Glance series aims to collect, present and disseminate accurate and relevant statistical information linked to international primary commodity markets in a clear, concise and reader-friendly format. This edition is specifically dedicated to the shale gas problem.